Speckled brain lesions in Incontinentia Pigmenti patients with acquired brain syndromes. (July 2021) - RR, Pravin; Douch, Catherine; Aan Koh, Mark Jean; Lai, Angeline H M; Lim, CC Tchoyoson; Hartley, Louise; Thomas, Terrence; Yeo, Tong Hong
Abstract: Incontinentia Pigmenti (IP) is a neurocutaneous syndrome, with malformations of cortical development and neurodevelopmental delay in some patients. Neonates with IP may develop acute encephalopathy with multifocal ischemic brain lesions with a speckled pattern on diffusion-weighted magnetic resonance imaging (MRI). We observed a similar MRI pattern in 4 female patients with IP who presented with childhood acute encephalopathy syndromes. These patients, aged 9 days to 13 years old, had acute neonatal encephalitis, Influenza A virus related acute necrotizing encephalopathy (ANE) of childhood, Influenza B virus related acute encephalopathy with biphasic seizures and late restricted diffusion (AESD) and acute disseminated encephalitis (ADEM) with transverse myelitis (TM). These lesions could possibly reflect the white matter changes in IP patients with encephalopathy.